Youth at risk in Latin America and the Caribbean : understanding the causes, realizing the potential - Cunningham, Wendy V. (Directions in development (Washington, D.C.). Human development., 2008)
Youth at Risk in Latin America provides evidence-based guidance to policymakers that will help increase the effectiveness of their youth investment program. Drawing on the authors' detailed analyses, the book describes twenty-three policies and programs that youth development experts agree are the basis of a quality youth development portfolio, from early childhood development programs to parent training to cash transfers for positive behaviors. It also lays out strategies for implementing this effective youth portfolio in a budget-constrained environment by reallocation of resources away from.